Development Of A Wireless Sensor Network For Smart Building Monitoring In UTP - Yee , Jia Xin (IRC, 2019)
The energy consumption of Universiti Teknologi PETRONAS (UTP) has been increasing significantly over the past years, primarily due to the ineffective building monitoring system and lacking of conservation behaviors among the community. With the proliferation of Internet of Things (IoT) devices, a new approach in monitoring and controlling of these energy consumption has been introduced. The technologies including of Wireless Sensor Network (WSN), has changed the management of conventional buildings by enforcing an intelligent utilization of electrical appliances with respect to user preferences, which significantly lowers down the energy consumption. However, its relatively high cost of implementation has hindered its integration in UTP campus